Proximity to Heavy Traffic Roads and Patient Characteristics of Late of Onset Asthma in an Urban Asthma Center - Lin, Ting-Yu; Lin, Horng-Chyuan; Liu, Yun-Sheng; Lo, Yu-Lun; Wang, Chun-Hua; Chang, Po-Jui; Lo, Chun-Yu; Lin, Shu-Min (Frontiers in Medicine, 2021)
Background: Traffic-related pollution is associated with the onset of asthma and the development of different phenotypes of asthma. Few studies have investigated the association between traffic proximity and late-onset of asthma (LOA) and early-onset asthma (EOA). This study was conducted to investigate the associations of LOA phenotypes with a function of the distance between residence and heavy traffic roads (HTRs). Methods: The study group consisted of 280 patients who were (LOA: 78.4%) recruited consecutively from a pay-for-performance asthma program to clarify the patient characteristics and proximity to HTRs within 1,000 m from their residences between EOA and LOA in three urban centers in Taiwan. The subsequent analysis focused on patients with LOA (n = 210) linking phenotypes and distance to HTRs. Results: Subjects with LOA tended to be older than those with EOA and had shorter asthma duration, poorer lung function, lower atopy, and less exposure to fumes or dust at home. Patients with LOA were more likely than those with EOA to live within 900 m of two or more HTRs (14.3 vs. 3.4%, p = 0.02). Among patients with LOA, minimum distance to an HTR was negatively associated with numbers of specific IgE as well as positively associated with the age of onset and body weight significantly. A higher proportion of patients with atopy (26.3 vs. 20.6%, p = 0.001. odds ratio [OR]: 2.82) and anxiety/depression (21.0 vs. 18.1%, p = 0.047. OR: 1.81) and a trend of lower proportion of patients with obese (5.7 vs. 12.4%, p = 0.075) were found to be living within 900 m from HTRs. Conclusions: Late-onset of asthma (LOA) tended to live in areas of higher HTR density compared to EOAs. Among patients with LOA living close to HTRs, the interaction between traffic-related pollution, allergy sensitization, and mood status were the factors associated with asthma onset early. Obesity may be the factor for later onset who live far from HTRs.